Electrical Characterization of Engineering Materials - Mohammad A. Alim (Active and Passive Electronic Components)
Engineering material systems for smart components and novel device applications require a thorough understanding on the structure-property-processing relationships to optimize their performance. The factors determining performance characteristics of the multi-phase/component heterogeneous polycrystalline hybrid (MPCHPH) systems are not identical to devices based on single-crystal/single-junction (SCSJ) technology. Performing SCSJ-like data-analysis on the MPCHPH systems can lead to confusion in delineating simultaneously operative phenomena when “physical geometrical factors”are used in normalizing the as-measured electrical parameters or electrical quantities. Such an analytical approach can vitiate interpretation when microstructural inhomogeneity plays a key role in determining the electrical path. The advantage of using the as-measured electrical parameters or electrical quantities constituting the “immittance function” is emphasized. The “state of normalization” using physical geometrical factors can only be executed for a specific phenomenon when isolated from the total electrical behavior.